Recent Trends in Humanities, Literature, Sociology and Psychology (Volume 2) - Rahul Ratnakar Mahamuni,; Grishma Khobragade,; Thakur Poornima, (AG Volumes, 2022)
What makes an individual a valuable employee and a pleasant coworker is a combination of hard and soft skills. The distinction between hard and soft skills is important. Communicating effectively, protecting one's intellectual property, and advancing one's career all need a solid foundation in soft skills. Interpersonal and personal qualities are examples of soft skills that contribute to a person's success in social situations, at work, and in their professional lives. There are a wide variety of "soft skills" that are essential in the modern workplace. Therefore, a person's soft skills development should start while they are still in school, so that they may succeed both in the classroom and in their future careers.